Identification of Fly Larvas in White Rats (Rattus norvegicus) Carcass Treated with Various Dose of Organophospate - Indra Putra, Ichsan Luqmana; Budiarti, Maolinda (Jurnal Veteriner; Vol 23 No 4 (2022)DO - 10.19087/jveteriner.2022.23.4.488, 2022)
The growth of flies on the carcass could be an indicator in estimating Post Mortem Interval. The aim of this study was to determine the type of flies and their abundance on the carcass of white rats (Rattus norvegicus) given various doses of diazinon’s organophosphate poison. This research was an experimental study using 12 female wistar white rats, aged 2-3 months, weighing 150-200 g. This study consisted of four treatments with three repetitions of each treatment. Variations in the dose of organophosphate given were treatment A (1.5 mL), B (2.5 mL), and C (3.5 mL). The parameters observed included the types and abundance of flies on the carcasses of white rats that were treated with organophosphate poisoning at different doses. Data analysis was carried out including the normality test, then continued with the homogeneity test and finally the analysis of variance test was carried out and the test results were not significantly different. The types of flies found on the carcass were Sarcophaga haemorrhoidalis, Chrysomya albiceps, C. megacephala and C. bezziana. The highest average abundance was S. haemorrhoidalis (34.3 larvae) and the lowest average abundance of fly larvae was C. bezziana (16.3 larvae). The conclusion of this study was that the variation in the dose of organophosphate does not affect the type, abundance and time of appearance of fly larvae on the carcass.